Transmission of α-synuclein seeds in neurodegenerative disease: recent developments - Karpowicz, Richard J. (Lab Invest, 2019)
Cell-to-cell transmission of proteopathic alpha-synuclein (α-syn) seeds is increasingly thought to underlie the progression of neurodegenerative diseases including Parkinson’s disease, dementia with Lewy bodies, multiple system atrophy, and related synucleinopathies. As such, it is important to understand the chemical and biological relationships between cells and pathological aggregates of α-syn. This brief review updates our understanding of the templated spread of α-syn pathology in neurodegenerative disease from the perspective of proteopathic α-syn seeds, including how these seeds are processed by cells as well as their effects on cellular function. Recent advances in understanding the conformations of α-syn seeds are highlighted, and the possible structural basis for the observed heterogeneity of synucleinopathies is discussed. Finally, we propose the possibility that some known risk factors for synucleinopathies may in fact potentiate the cell-to-cell transmission of α-syn pathology via imbalances in interrelated cell biological processes.